An economic study of smallholder dairy farms in Muranga District, Kenya - Schaik, G. van; Perry, Brian D.; Mukhebi, A.W.; Gitau, G.K.; Dijkhuizen, A.A. (Elsevier, 1996)
The Murang'a District is situated in central Kenya and is a highland area with a high potential for dairy production. This study was carried out to evaluate the performance of smallholder dairy farms by analysing available data and by simulation modelling. Eighteen case farms were selected non-randomly on the basis of differences in reported milk production, based on the amount of milk delivered to a dairy society. Data of these smallholder dairy farms were collected by means of a questionnaire and included all farm resources and enterprises. The Technology Impact Evaluation Simulator (TIES), a Monte Carlo computer simulation model, provides a method for evaluating the financial and economic impacts of technology changes on a whole-farm basis, and explicity incorporates risk. The simulation of each case farm in the Murang'a District with TIES gave an indication of the variation in economic performance of these farms. A sensitivity analysis on the economic terms pointed out the key indicators for successful farm performance. The smallholder dairy farms investigated differed in farm performance - itself strongly influenced by the performance of the dairy enterprise of the farm. Milk production and calving interval were the main indicators describing the performance of the dairy enterprise and, through that overall farm performance. Both milk production and calving interval were influenced by the amount of concentrates fed-suggesting that feeding concentrates is an important indicator of high farm performance. The influence of health-services costs on farm performance was not significant. Off-farm income also influenced overall farm performance; farms heavily dependent on off-farm income were often inefficient in their dairy enterprise.